The influence of creativity , innovation , and flexibility with technology as a success factor for culinary MSMEs - Widjaya, Oey Hannes; The, Lianah; Royvandi Pramadhika (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
The culinary industry is one of the fastest-growing business sectors in Indonesia in recent years. Creativity, innovation, and flexibility are essential characteristics of originality or authenticity that an entrepreneur must possess to increase income, expand their business, and compete effectively in the market. MSMEs in the culinary sector must develop strategies that have broad implications for creativity, innovation, and flexibility, with technology serving as a supporting factor for business success. This study aims to examine the role of creativity, innovation, and flexibility, with technology as a contributing factor to the success of culinary MSMEs in Grogol Petamburan, West Jakarta. The sample for this study consists of 100 culinary MSME entrepreneurs from the Grogol Petamburan sub-district, West Jakarta. Four hypotheses are tested, focusing on the influence of creativity, innovation, flexibility, technology in innovation, and business success. The sampling technique employed is a non-probability sampling method using a purposive sampling technique, with data collected through online questionnaires via Google Forms. The data is then processed using PLS-SEM. The study results indicate that creativity and innovation do not have a significant effect on the business success of MSME entrepreneurs. However, flexibility and technology in innovation have a positive and significant impact on their business success.